Finance Bundling and Finance Transformation Shared Services Next Level - Keuper, Frank; Lueg, Kai-Eberhard.; SpringerLink (Online service) (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer Gabler, 2013)
In managerial literature the challenges of ramping-up, growing and enhancing a (Finance) Shared Services Organization are regularly neglected. Therefore, the compilation will address two objectives: First, based on a generic phase model of an SSO$1 (Bs development, frequently arising questions related to the management of SSOs shall be systematically discussed and practicable solutions derived. Secondly, a picture of the future of SSOs shall be elaborated, resulting in new future management implications. Content Strategic Management and Governance Aspects of a Global (Finance) SSO Transformation and Transition Programs Process and Performance Management Change and Human Resources Management Selected Enablers and Prerequisites for a Successful Development of an SSO Future Trends and New Shared Service Areas Target Groups Decision-makers and practitioners in business Lecturers and students of business administration The Editors Prof. Dr. rer.pol. habil. Frank Keuper is director of the Steinbeis Center of Strategic Management and holder of the chair of Business Administration, particularly Convergence Management and Strategic Management, Steinbeis University Berlin. Kai-Eberhard Lueg is Chief Financial Officer Global Shared Services Siemens AG and heads the global shared accounting organization.s
Keywords: Economics; Industrial management; Economics/Management Science; Management/Business for Professionals; Finance/Investment/Banking.